Perlindungan Hukum terhadap Korban Penipuan Jual Beli Online - Bagus Andi Dwi Prakoso; I Nyoman Sujana; Luh Putu Suryani (Warmadewa Press, 2020)
Currently, the internet is often used as a means of trading in Indonesia, which often leads to cybercrime crimes, from fraud in trading to fraudulent objects of buying and selling online, requiring legal preservation. What is the form of legal preservation of the object of fraud in online trading? How do criminal sanctions for fraudsters roll out online? These two questions are the problems examined in this study. This study was designed using a normative legal research design. The results of research and assessment can be concluded that legal protection for victims of online buying and selling fraud is essentially carried out by non-penal and penal channels. Legal protection using the penal line can be realized through repressive measures, and non-penal through preventive measures. In repressive actions, objects can be reported by visiting legal institutions for further processing. In a preventive measure, outreach is held about legislation and legal understanding of the ways and culture of using technology so that there is no response to requests for information via e-mail. Matters that affect legal protection for victims of online bladder selling are aimed at the lack of proper facilities and infrastructure, namely the inadequate extension of statutory regulations related to cybercrime to the public. Quality of law enforcement officers and the culture of the people who are not interested in making reports and testimonies. Fraud in trading with online media within the scope of legal regulations has been regulated using positive law in Indonesia, namely in the Criminal Code and the Electronic Information and Technology Law (UU ITE). Although the Law has not been able to deter all the perpetrators concerned, seeing the Principle of Legality in Article 1 of the Criminal Code and the opinion of criminal experts that online defamation is a crime, and therefore it is definitely against the law. Then it must be held accountable for the actions when it is done.